Correspondencia entre la estrategia comunidad de indagación y la formación ciudadana en el contexto del modelo educativo relacional (2022)
Education is carried out from a sociopolitical framework with a purpose of the same scope, that is, every educational act is a social and political act. Citizen education is one of the main reasons for being of any educational institution, since it is citizenship, the category that encompasses the ideal of the subject to be educated. In this context, this paper aims to analyze the correspondence between the community of inquiry strategy and citizen training in the context of the relational educational model. The study is based on a rationalist-deductive approach, mixed paradigm (qualiquantitative). The research is contextualized in the María Josefa Escobar Educational Institution of Itagüí, Antioquia, through two stages of research: the first of a theoretical nature, where documents such as the Institutional Educational Project, the Evaluation and Promotion System are analyzed and, finally, the Coexistence Manual; and the second of an empirical nature through the application of a field design to observational units, such as students and teachers. The findings allow us to show that the community of inquiry becomes a pedagogical and didactic proposal which nourishes the relational educational system, both at a theoretical level, due to the foundations on autonomy and the curriculum, as well as at a practical level, insofar as generates a culture of decisions, actions, horizontal, dialogical, and constructive communications, thus allowing a contextualized and localized citizen formation with a current sociopolitical sense.